2017
DOI: 10.4103/sni.sni_322_17
|View full text |Cite
|
Sign up to set email alerts
|

Simple training tricks for mastering and taming bypass procedures in neurosurgery

Abstract: Background:Neurosurgeons devoted to bypass neurosurgery or revascularization neurosurgery are becoming scarcer. From a practical point of view, “bypass neurosurgeons” are anastomosis makers, vessels technicians, and time-racing repairers of vessel walls. This requires understanding the key features and hidden tricks of bypass surgery. The goal of this paper is to provide simple and inexpensive tricks for taming the art of bypass neurosurgery. Most of these tricks and materials described can be borrowed, donate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…21,22 Actions that do not fulfil their objective and time taken to perform the bypass Actions that do not achieve their objective consume time and, more importantly, disturb eye-hand orientation, the flexibility of the surgeon and self-confidence. 2,3,13,23,24 Although time is always measured during a bypass procedure, it is difficult to quantify the most optimal cut-off. The criterion of speed is not as important as the achievement of speed in combination with the other evaluated factors, i.e., achieving a score of 1 for completing the procedure in ≤ 20 minutes is more…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Actions that do not fulfil their objective and time taken to perform the bypass Actions that do not achieve their objective consume time and, more importantly, disturb eye-hand orientation, the flexibility of the surgeon and self-confidence. 2,3,13,23,24 Although time is always measured during a bypass procedure, it is difficult to quantify the most optimal cut-off. The criterion of speed is not as important as the achievement of speed in combination with the other evaluated factors, i.e., achieving a score of 1 for completing the procedure in ≤ 20 minutes is more…”
Section: Discussionmentioning
confidence: 99%
“…Vital steps need to be taken to ensure the quality of vascular anastomosis during bypass surgery. [1][2][3][4][5][6][7][8][9][10][11] It is critical to ensure that the time taken to minimise blood flow during the procedure is as brief as possible as this is a significant source of stress for the neurosurgeon 12,13 and can impact on the quality of suturing.…”
Section: Introductionmentioning
confidence: 99%
“…The trainees experience a different levels of stress and anxiety before and during surgical procedures [3,12,22]. Neurosurgical operations hold high level of anxiety, demands certain level of hand-eye coordination, and fine manipulation [4,6,8,17,36].…”
Section: Discussionmentioning
confidence: 99%
“…A similar notion of home-based learning has been alluded to in the neurosurgical literature, 22 though the described method was limited to training entirely via suturing strands of gauze, without expansion into more translatable models. Hafez et al 23 reviewed important technical pearls for performing cerebral bypass and also suggested a rigorous training curriculum: at least 1 hour per day using 7-0 and 8-0 sutures (3 months); another minimum 1 hour per day using 9-0 suture (3 months); a minimum 1 hour per day with 10-0 suture, focusing on speed (270 hours to achieve "expertise"); and finally, at least 1 hour biweekly to maintain expertise. We propose an expansion specific to neurosurgical training, with detailed training regimens and guidelines for both home and clinical training, that extends beyond bypass/microsuture training.…”
Section: Importance Of Adjunct Training Modalitiesmentioning
confidence: 99%